2013
DOI: 10.1155/2013/809234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Extracts ofGraptopetalum paraguayenseon Blood Pressure, Fasting Glucose, and Lipid Profiles of Subjects with Metabolic Syndrome

Abstract: This study was aimed to investigate the effects of water extracts of Graptopetalum paraguayense (WGP, 4 g/d) on blood pressure, blood glucose level, and lipid profiles in subjects with metabolic syndrome (MS). Participants with MS (n = 54) were randomly assigned to the placebo (n = 28) and WGP groups (n = 26), and the intervention was administered for 12 weeks. Systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting glucose (FG), lipid profiles (total cholesterol (TC), triglyceride (TG), low den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In our previous study, we found a significant reduction in blood glucose and lipid profiles after WGP supplementation in the subjects with MS. Additionally, in the present study; we demonstrated anti‐inflammatory effects of WGP. Based on these results, we suppose that WGP exerts these beneficial effects on MS because of its antioxidant capacity . It is interesting to note that some of our subjects in this study were under anti‐diabetic, antihypertensive, or lipid‐lowering medications (Table ), but the proportion of medications was not significantly different between the placebo and WGP groups.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…In our previous study, we found a significant reduction in blood glucose and lipid profiles after WGP supplementation in the subjects with MS. Additionally, in the present study; we demonstrated anti‐inflammatory effects of WGP. Based on these results, we suppose that WGP exerts these beneficial effects on MS because of its antioxidant capacity . It is interesting to note that some of our subjects in this study were under anti‐diabetic, antihypertensive, or lipid‐lowering medications (Table ), but the proportion of medications was not significantly different between the placebo and WGP groups.…”
Section: Resultsmentioning
confidence: 55%
“…Many studies have demonstrated its biological activities, including the inhibition of tyrosinase, the prevention of lipid peroxidation; and its antihypertensive, hepatoprotective, and neuroprotective effects . Recently, we demonstrated that water extract of G. paraguayense (WGP) could significantly reduce the levels of blood pressure, blood glucose, and blood lipids in MS patients . As MS is considered to be a chronic inflammatory status, it is worth to examine the anti‐inflammatory effect of G. paraguayense in MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…; Yen et al . ). Carboxymethyllysine (CML) is an advanced glycation end product (AGE) that causes pancreatic damage, and diabetes can be controlled by G. paraguayense (Lee et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Yen et al . ). In diabetic patients, a high methylglyoxal concentration in the blood was found to be positively correlated with hyperglycemia (Cheng et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation